Radiolabeled Monoclonal Antibody Against Colony-Stimulating Factor 1 Receptor Specifically Distributes to the Spleen and Liver in Immunocompetent Mice - Waaijer, Stijn J. H.; Suurs, Frans V.; Hau, Cheei-Sing; Vrijland, Kim; de Visser, Karin E.; de Groot, Derk Jan A.; de Vries, Elisabeth G. E.; Lub-de Hooge, Marjolijn N.; Schröder, Carolina P. (Frontiers in oncology, 2021)
Macrophages can promote tumor development. Preclinically, targeting macrophages by colony-stimulating factor 1 (CSF1)/CSF1 receptor (CSF1R) monoclonal antibodies (mAbs) enhances conventional therapeutics in combination treatments. The physiological distribution and tumor uptake of CSF1R mAbs are unknown. Therefore, we radiolabeled a murine CSF1R mAb and preclinically visualized its biodistribution by PET. CSF1R mAb was conjugated to N -succinyl-desferrioxamine ( N -suc-DFO) and subsequently radiolabeled with zirconium-89 ( 89 Zr). Optimal protein antibody dose was first determined in non-tumor-bearing mice to assess physiological distribution. Next, biodistribution of optimal protein dose and 89 Zr-labeled isotype control was compared with PET and ex vivo biodistribution after 24 and 72 h in mammary tumor-bearing mice. Tissue autoradiography and immunohistochemistry determined radioactivity distribution and tissue macrophage presence, respectively. [ 89 Zr]Zr-DFO- N -suc-CSF1R-mAb optimal protein dose was 10 mg/kg, with blood pool levels of 10 ± 2% injected dose per gram tissue (ID/g) and spleen and liver uptake of 17 ± 4 and 11 ± 4%ID/g at 72 h. In contrast, 0.4 mg/kg of [ 89 Zr]Zr-DFO- N -suc-CSF1R mAb was eliminated from circulation within 24 h; spleen and liver uptake was 126 ± 44% and 34 ± 7%ID/g, respectively. Tumor-bearing mice showed higher uptake of [ 89 Zr]Zr-DFO- N -suc-CSF1R-mAb in the liver, lymphoid tissues, duodenum, and ileum, but not in the tumor than did 89 Zr-labeled control at 72 h. Immunohistochemistry and autoradiography showed that 89 Zr was localized to macrophages within lymphoid tissues. Following [ 89 Zr]Zr-DFO- N -suc-CSF1R-mAb administration, tumor macrophages were almost absent, whereas isotype-group tumors contained over 500 cells/mm 2 . We hypothesize that intratumoral macrophage depletion by [ 89 Zr]Zr-DFO- N -suc-CSF1R-mAb precluded tumor uptake higher than 89 Zr-labeled control. Translation of molecular imaging of macrophage-targeting therapeutics to humans may support macrophage-directed therapeutic development.